Evaluasi Karakteristik Keimaman Menurut Maleakhi 2:1-9 Dan Relevansinya Bagi Kepemimpinan Jemaat Masa Kini - Well Therfine Renward Manurung (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2025)
Malachi 2:1-9 contains God’s strong reprimand towards the priests as leaders of the congregation for living unrighteously, not honoring, and not listening to His word. This context is relevant today, where many church leaders have become stumbling blocks and there is deviation in service. The gap in previous research, with its diverse perspectives on Malachi 2:1-9, forms the background for this research. The aim of this research is to discover the principles or characteristics of church leadership from the perspective of Malachi 2:1-9, which can then be applied (made relevant) in modern church leadership. This research uses qualitative methodology with biblical theology and an exegetical approach to Malachi 2:1-9. The analysis focuses on constructing an interpretation of the prophetic literary text. This study evaluates and unearths two areas in Malachi 2:1-9: first, priestly characteristics in Malachi 2:1-9, which include attributes of a teacher, exemplary conduct and faithfulness; second, priestly characteristics relevant to contemporary church leadership, namely faithful devotion to God, guarded speech, doctrinally sound teaching and diligent preservation of knowledge.